Project Hyperopic Power Prediction II: The Effects of Second Eye Refinement Methods on Prediction Error in Hyperopic Eyes. (3rd August 2022) - Wendelstein, Jascha A.; Reifeltshammer, Sophia A.; Hoffmann, Peter C.; Fischinger, Isaak; Mariacher, Siegfried; Bolz, Matthias; Langenbucher, Achim; Hirnschall, Nino
Abstract: Purpose: The purpose of the study was to evaluate the potential accuracy of different second eye refinement methods in a patient cohort with short axial eye length to assess the performance of intraocular lens (IOL) power calculation schemes in high hyperopes. Methods: The study design was a single-center, single-surgeon retrospective consecutive case series. The setting of the study was in Augen- und Laserklinik, Castrop-Rauxel, Germany. Patients were assessed after uneventful bilateral cataract surgery implanting either spherical (SA60AT) or aspheric (ZCB00) IOLs. Inclusion criteria were an axial eye length of ≤21.5 mm and/or emmetropizing IOL power of >28.5 dpt. Outcome measures were the mean absolute prediction error (MAE), median absolute prediction error, mean prediction error with standard deviation, median prediction error, and the percentage of eyes with an absolute prediction error (absPE) within 0.25 dpt, 0.5 dpt, 0.75 dpt, or 1.0 dpt. Second eye refinement was performed using the first eye prediction error, either with a correction coefficient of 0.50 (SER1), or an individual coefficient optimized for MAE. Results: A total of 55 patients were assessed. A statistically significant reduction in the absPE after the application of SER1 was observed in 9 of 13 formulae. The SER1 refined Hoffer Q, refined Holladay I, refined Holladay II, refined Kane, refined Okulix, and refined PEARL-DGS provided a smaller absPE than other methods. Conclusion: In this patient cohort with a short axial eye length, the second eye refinement led to a lower MAE in almost all formulae. The use of refinement in Kane, Okulix, PEARL-DGS, and Castrop formulae exhibited the lowest MAE.